Crescimento e infraestrutura: três ensaios com dados em painel - Monteiro, Vitor Borges (2011)
The thesis consists of three chapters that have in common estimation models for panel data. The first chapter titled "Energy Consumption, GDP per capita and Exports: Evidence of long-term causality in a panel for the Brazilian States" analyzes the order of causality between the variables and then checks the long-term elasticities using the methodology FMOLS. It shows that GDP per capita is caused by their own past achievements, by consumption of electricity and exports. The consumption of electricity and exports, only are not caused by GDP per capita. Through the model FMOLS were estimated elasticities of long-term. The 1% increase in energy consumption and exports increased respectively 0.07% and 0.04 % in GPD per capita. The second chapter, entitled "Sustainability of Health Expenditure and Sanitation in Brazil: an analysis with Panel Data for the period 1985 to 2005" examines the sustainability of Health Expenditure and Sanitation of the states and the Federal District of Brazil, during the period 1985 to 2005. For this, we use the ratio of Expenditure by Function (Health and Sanitation) and GDP. The unit root tests for panel data refute the null hypothesis of presence of the unit root (the stochastic process is stationary) at 5% significance level. Accordingly, we can infer that the policy of health expenditure as a proportion of GDP remained almost stable (sustainable) over the period in question. The third chapter entitled "Formation of Convergence Clubs and Analysis of the Determinants of Economic Growth" support the formation of 10 clubs of convergence for a sample of 112 countries with per capita GPD data from 1980 to 2014 using the Phillips and Sul methodology (2007). Logged clubs and estimated a panel to investigate the impact of macroeconomic variables in the dynamics of economic growth rate through the Arellano and Bond model (1991) showed that: i) Inflation impacts the growth rate negatively, with effect greater for clubs that converge to a higher level of per capita income ii) imports as a proportion of GDP have positive relationship with the growth rate of per capita income for the countries belonging to clubs intermediaries, and a negative effect for other clubs iii) Exports as a proportion of GDP have a positive effect for all clubs, but is more pronounced for clubs that converge to a lower level of income and iv) international reserves have a positive effect for clubs that converge to high levels of income and a negative effect on clubs that converge to low levels of income.